Analysis and planning of flood zones. Case study: Ramon’s Stream, Santiago de Chile - Cadierno Gutiérrez, Jon (Geographicalia, 2015)
The present work addresses the analysis and planning of an area affected by the floods of Ramon’s Stream, in Santiago de Chile. From the analysis of the current normative framework about flood zones, the elaboration of a diagnosis about the flow behaviour and the evaluation of the law compliance and the adaptation of the soil uses in the restricted areas demarcated by the land management plans, a series of suggestions for the elaboration of a new planning for flood zones is presented. The basis of these alternatives is the partial recovery of the River Territory, thus suggesting some solutions coming from land management which reduce the risk of the exposed population, mainly through the elimination of obstacles in order to let the swellings reoccupy the areas that belong to the river dynamics.